Avaliação da integridade neurológica periférica e tratamento sinérgico de fotobiomodulação e ultrassom terapêutico em pacientes com Diabetes Mellitus (tipo II): estudo clínico randomizado e duplo cego - Bruno, Juliana da Silva Amaral (Universidade Federal de São Carlos, 2025)
Diabetes Mellitus (DM) is a chronic disease that currently affects approximately 589 million adults worldwide, aged 20 to 79 years. Alarming projections indicate that by 2050, this number could exceed 853 million individuals in the same age group. Diabetic peripheral neuropathy (DPN) is one of the most common complications of DM, characterized by a set of syndromes with diverse clinical and subclinical manifestations. Neurological damage tends to be extensive, broadly compromising the peripheral nervous system in its sensorimotor and autonomic components. Pain presents with variable intensity, being a constant complaint, commonly described as tingling, burning, or a sensation of needles in the extremities, frequently accompanied by abnormal sensory alterations such as allodynia and hyperalgesia. Early diagnosis of DPN and its continuous monitoring are fundamental, as they promote the education and awareness of the diabetic patient, in addition to contributing to delaying or minimizing more serious complications throughout the progression of the disease. This study aimed to compare diabetic neuropathy screening techniques (conventional versus DPN Check®). This study aimed to evaluate the effects of the combined application of photobiomodulation and therapeutic ultrasound in the treatment of diabetic foot ulcers (DFU) in early stages, aiming to prevent severe complications such as the development of diabetic foot. Sixty participants were recruited, assessed using various DFU screening tools, and randomly assigned to two groups: a treatment group and a control group. The treatment group received bilateral combined photobiomodulation and therapeutic ultrasound stimulation in the sural nerve region (sensory nerve), with the following parameters: continuous laser, 100 mW power, 808 nm wavelength, and therapeutic ultrasound with a frequency of 1 MHz, pulsed mode (50% duty cycle), secondary frequency of 100 Hz, intensity of 0.8 W/cm², for 6 minutes on each sural nerve, with rotational movement of the transducer, and a frequency of 24 sessions (twice a week, on alternate days).The control group received minimal ultrasound emission (0.1 W/cm2) and no laser emission. The results of the objective assessments performed using the DPN Check® demonstrated that, in the treatment group, the "Normal" classification increased from 7% to 80% in 90 days, while the "Moderate" classification, predominant at the beginning at 70%, was reduced to 7% in the same period. In the subjective assessments, the "Normal" classification increased from 0% to 80%, and the "Moderate" classification decreased from 60% to 0% for the treatment group; conversely, in the control group, the "Normal" classification increased only from 3% to 7%, while the "Moderate" classification remained at 70% in the objective assessments. In the subjective assessments, there was no change in the "Normal" classification (remaining at 0% from beginning to end). It was concluded that combined treatment with photobiomodulation and therapeutic ultrasound for diabetic peripheral neuropathy promotes a significant reduction in symptoms and improvement in sensitivity in patients with diabetic peripheral neuropathy; in contrast, the control group did not show significant improvement in the same parameters.
Assessment of peripheral neurological integrity and synergistic treatment with photobiomodulation and therapeutic ultrasound in patients with Diabetes Mellitus (type II): a randomized, double-blind clinical trial
Keywords: Neuropatia; Diabetes Mellitus; Rastreio; Fotobiomodulação; Ultrassom Terapêutico; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar